2018
DOI: 10.18632/oncotarget.23961
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt-β-catenin signaling regulated MRTF-A transcription to activate migration-related genes in human breast cancer cells

Abstract: MRTF-A is a transcriptional co-activator being critical for multiple processes including tissue fibrosis and cancer metastasis. The Rho-actin signaling stimulates the nuclear translocation and transcriptional activity of MRTF-A with little effect on the expression of MRTF-A gene. High expression of MRTF-A was observed in pancreatic cancer tissues and in TGF-β treated breast cancer cells. However, the mechanism for the upregulation of MRTF-A gene remains unclear. In this study, we showed that the transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…MRTF is also regulated at the transcriptional level, although the underlying mechanisms remain largely uncharacterized. Nonetheless, β-catenin has been recently identified as an inducer of the MRTF gene [ 127 ], suggesting that β-catenin not only stabilizes MRTF but also enhances its synthesis. While this observation was made in a tumor context, it may well be relevant in organ fibrosis as well.…”
Section: Regulationmentioning
confidence: 99%
“…MRTF is also regulated at the transcriptional level, although the underlying mechanisms remain largely uncharacterized. Nonetheless, β-catenin has been recently identified as an inducer of the MRTF gene [ 127 ], suggesting that β-catenin not only stabilizes MRTF but also enhances its synthesis. While this observation was made in a tumor context, it may well be relevant in organ fibrosis as well.…”
Section: Regulationmentioning
confidence: 99%
“…Noncanonical pathways include RhoA/ROCK1, PI3K/Akt, Wnt/β-catenin, MAPK/p38, or MAPK ERK1/2, all of which mediate different effects of TGF-β on tumor cells 35 , 45 , 46 . Thus, we assessed the TGF-β-induced change in PD-L1 expression in the absence or presence of various inhibitors, including the selective p38 MAPK inhibitor doramapimod (DORA), the Akt inhibitor AKTi-1/2 (AKTi), the MEK inhibitor U0126, the Rho kinase inhibitor Y-27632 and β-catenin siRNA.…”
Section: Resultsmentioning
confidence: 99%
“…4i ). It has been reported that β-catenin and Rho can regulate the expression and nuclear localization of MRTF-A, respectively 35 , 47 . AKT and p38 provoke the phosphorylation and consequent activation of p65 48 , 49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway is critical in human tumorigenesis by regulating cellular proliferation and differentiation in vertebrates as well as invertebrates via the β-catenin destruction complex [5]. Impaired regulation of the Wnt-dependent target genes has been shown to be involved in the occurrence of several other human cancers and its abnormal expression has been associated with tumorigenesis, for example, breast cancer, endometrial cancer [7], colon carcinoma [8], medulloblastoma [9], melanoma [10], hepatocellular carcinoma [11] and gastric cancer [12]. In addition, studies have shown that complete inactivation of AXIN1 function led to early embryonic lethality in mice.…”
mentioning
confidence: 99%